Legal Implications of the Assignment of Trademark Ownership in Franchise Agreements - Aulia, Irza Akhlis; Santoso, Budi (Dinasti Research, 2025)
Franchising is a business model that heavily relies on trademarks as the primary identity and asset in the relationship between franchisors and franchisees. One of the legal issues that frequently arise in practice is the change or transfer of trademark ownership, which can significantly impact the continuity of franchise agreements. The transfer of ownership without clear regulations can create legal uncertainty for franchisees, particularly concerning their rights to use the trademark and the sustainability of their businesses. Therefore, this study aims to analyze the legal implications of trademark ownership transfers in franchise agreements based on the regulations applicable in Indonesia, such as Law No. 20 of 2016 on Trademarks and Geographical Indications and Government Regulation No. 42 of 2007 on Franchising.This research employs a normative legal research method using a statutory and conceptual approach. The findings indicate that the lack of clear regulations regarding the transfer of trademark ownership in franchise agreements can lead to various issues, including changes in business policies by the new owner, unilateral termination of the franchise relationship, or even the loss of franchisees' rights to use the developed trademark. These issues pose financial risks and business uncertainty for franchisees. To mitigate these problems, franchise agreements must include explicit clauses governing the mechanism for trademark ownership transfer to protect franchisee rights and interests.This study recommends strengthening franchising regulations with more specific provisions regarding trademark ownership transfer and encouraging stricter supervision by the Directorate General of Intellectual Property (DJKI). By ensuring greater legal certainty, it is expected that the franchise system in Indonesia can develop more transparently and fairly while providing optimal protection for all parties involved in franchise agreements.